Internet of Things for Monitoring Infusion Fluids in Intravenous Chemotherapy Patients: Literature Review - Herlin Ajiyanti; La Ode Abdul Rahman (Indonesian Journal of Sport Management and Physical Education, 2022)
Administration of intravenous chemotherapy drugs to cancer patients requires sophisticated infusion fluid monitoring tools so that the therapy process is smooth, safe, and comfortable. Internet-based technology of things to monitor intravenous chemotherapy drug infusion fluids more accurately and easily. Non-systematic review literature, using online data base: Elsevier (ScienceDirect), IEEE Xplore, ProQuest, Sage Journal with keywords: "internet of things" AND "infusion monitoring" AND "chemotherapy", "infusion monitoring system" with filter: " full text”, “Published in the last 5 years”, “journal” AND “2017-2022”. Literature review of 10 journals using the internet of things to accurately monitor infusion fluids is beneficial for chemotherapy patients. Making a monitoring system for chemotherapy drug infusions in Indonesia based on the internet of things that is accurate, easy and cheap.